2014
DOI: 10.4236/ce.2014.510089
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Collaboration: Cognitive Behavioral Interventions in Special Education and School Psychology

Abstract: Cognitive behavioral interventions (CBIs) attempt to affect behavior change by teaching relevant tasks that are based around strategies to correct cognitive distortions through the application of logic and the search for evidence. Goals are clearly specified; decisions are made on how to best meet specified goals and how to measure progress toward goals to provide feedback. The intervention is task-oriented and focused on problem-solving. This article provides a brief review of the theoretical tenets of CBIs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Sukhodolsky, Kassinove, and Gorman reported that cognitive behavioural therapy corrected anger in children and adolescents. The result of this study is also in line with the work of Banks, Squires, and Anhalt (2014), who worked on interdisciplinary collaboration: cognitive behavioural interventions in special education and school psychology.…”
Section: Discussionsupporting
confidence: 83%
“…Sukhodolsky, Kassinove, and Gorman reported that cognitive behavioural therapy corrected anger in children and adolescents. The result of this study is also in line with the work of Banks, Squires, and Anhalt (2014), who worked on interdisciplinary collaboration: cognitive behavioural interventions in special education and school psychology.…”
Section: Discussionsupporting
confidence: 83%
“…Focusing on the psychosocial and academic aspects in school is thought to have positive effects on students' well-being, learning environment and learning outcomes, to lower dropout rates and, in the long term, reduce mental health issues and decrease unemployment (Banks, Squires, & Anhalt, 2014;Holen & Waagene, 2014). Many researchers believe that collaboration across professions, that is, between teachers, nurses and social workers, is a necessary and viable tool in an educational world of increasing complexity (Mellin, 2009;Winitzky, Sheridan, Crow, Welch, & Kennedy, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…This may be a function of the study's focus on school-based services; those referred in medical settings may not be receiving services outside of the clinic. While collaboration between clinical or medical and school professionals are associated with increased service implementation (Banks et al, 2014), it is not legally required. To accommodate the multitude of avenues that lead to REM students receiving ADHD services, interdisciplinary collaboration with schools should increase.…”
Section: Discussionmentioning
confidence: 99%